Renal protective effect of a hydration supplemented with magnesium in patients receiving cisplatin for head and neck cancer - Takahiro Kimura; Taijiro Ozawa; Nobuhiro Hanai; Hitoshi Hirakawa; Hidenori Suzuki; Hiroshi Hosoi; Yasuhisa Hasegawa (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Our study analyzes the effect of magnesium supplementation on nephrotoxicity in patients receiving cisplatin for head and neck cancer. Methods We retrospectively reviewed the medical records of patients with head and neck cancer who received two doses of cisplatin (80 mg/m2) and 5-fluorouracil (800 mg/m2) 3 weeks apart from August 2008 to October 2012. The regimen prior to 2011 (crystalloid-only) involved the administration of 1000 mL of lactated Ringer’s solution on the day prior to cisplatin infusion and 2000 mL of continuous infusion of saline on the day of cisplatin infusion. The regimen after 2011 (magnesium-supplemented) did not involve hydration on the day before cisplatin administration but used 1000 mL of 0.9% saline with magnesium sulfate (20 mEq) administered for 3 hours before cisplatin infusion. Results Sixty-five patients were treated with the crystalloid-only regimen and 56 patients with the magnesium-supplemented regimen. The mean creatinine clearance in the magnesium-supplemented group decreased by 4.9 mL/kg/min, whereas that in the crystalloid-only group decreased by 15.0 mL/kg/min after two courses. In multivariate analysis, only magnesium-supplemented hydration was an independent predictive factor for preventing cisplatin-induced nephrotoxicity (odds ratio = 0.157, 95% confidence interval 0.030–0.670, P = 0.0124). Conclusion We demonstrated that an intravenous hydration regimen supplemented with magnesium prevented cisplatin-induced nephrotoxicity in patients with head and neck cancer.